2013
DOI: 10.1136/heartjnl-2013-304564
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of bleeding measured by Bleeding Academic Research Consortium (BARC) categorisation in patients undergoing primary percutaneous coronary intervention

Abstract: The present study demonstrated that bleeding events defined according to the BARC classification hierarchically correlate with 1-year mortality after admission for primary PCI. The strongest predictor of 1-year mortality is the BARC type 3b bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…6 Using this definition, TRI was associated with significantly less postprocedural bleeding and reduced mortality, which is consistent with previously published studies associating BARC bleeding and mortality. 35,36 In addition, the RIFLE investigators examined access site and non-access site bleeding; importantly, radial access significantly decreased access site bleeding (as would be expected) and had no effect on non-access site bleeding. This served as an internal control to support the effect of the randomized intervention (access site) on the outcome of bleeding.…”
Section: Is This Reduction In Bleeding Responsible For the Mortality mentioning
confidence: 91%
“…6 Using this definition, TRI was associated with significantly less postprocedural bleeding and reduced mortality, which is consistent with previously published studies associating BARC bleeding and mortality. 35,36 In addition, the RIFLE investigators examined access site and non-access site bleeding; importantly, radial access significantly decreased access site bleeding (as would be expected) and had no effect on non-access site bleeding. This served as an internal control to support the effect of the randomized intervention (access site) on the outcome of bleeding.…”
Section: Is This Reduction In Bleeding Responsible For the Mortality mentioning
confidence: 91%
“…Bleeding was classified according to the Bleeding Academic Research Consortium (BARC) classification. Cases with a BARC score >2 were recorded [18] .…”
Section: Clinical Endpointsmentioning
confidence: 99%
“…The standardized bleeding definition will be expected to help the physician to correctly analyze the bleeding events, to select an optimal treatment, and to objectively compare the results of multiple trials and registries. Recent trials have demonstrated that the BARC definition of bleeding was suggested to have a predictive value in regard to 1-year mortality that is comparable to that provided by traditional bleeding definitions [17][18][19].…”
Section: Characteristicsmentioning
confidence: 99%
“…The BARC criteria are a consensus-based report, rather than clinically based or laboratory-based assessments. According to previous large clinical trials to evaluate the validation of the BARC definition, bleeding complications as defined by BARC criteria were independently associated with an increased risk of 1-year mortality after PCI, and provided a predictive value in regard to 1-year mortality [17][18][19].…”
Section: Introductionmentioning
confidence: 99%